Real-world clinical and psychosocial outcomes among people with mild or moderate haemophilia A treated on-demand in the Italian CHESS II cohort: a real-world data analysis - Castaman Giancarlo; Mancuso Maria Elisa; Di Minno Matteo Nicola Dario; Sannino Luigi; Tempre Rosaria; Bendinelli Sara; Blenkiron Tom; Burke Tom; Grazzi Enrico Ferri (The Journal of Haemophilia Practice)
The burden of severe haemophilia A (HA) has been studied extensively owing to the higher bleeding frequency and associated treatment requirements, leaving a clear unmet need for research focused on the burden of mild and moderate HA.